2015
DOI: 10.5152/tjg.2014.5616
|View full text |Cite
|
Sign up to set email alerts
|

Location of rectal cancer as determined using rectal magnetic resonance imaging, and its relationship with pulmonary metastasis

Abstract: Background/Aims: The aim of this study was to evaluate the accuracy of 3-T magnetic resonance imaging (MRI) in locating rectal cancer, and to determine whether tumor location correlates with the incidence of pulmonary metastasis. Materials and Methods: A total of 146 patients with confirmed rectal adenocarcinoma underwent 3-T rectal MRI, and abdominal and chest computed tomography (CT) within 2 weeks of the endoscopic examination. We reviewed the distance between the mass and the anal verge recorded in the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The direct methods achieved the least bias, the highest precision, and the best correlation with rigid sigmoidoscopy among the three methods groups. The majority of previous studies have measured the tumor distance using multiple lines that reflect the anorectal curvature [2,6,[18][19][20][21][22][23][24]29]. However, in our study, the direct methods using a straight line demonstrated the best results; this corroborates the findings by Meylemans et al, who compared measurement methods using a straight line or multiple straight lines [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The direct methods achieved the least bias, the highest precision, and the best correlation with rigid sigmoidoscopy among the three methods groups. The majority of previous studies have measured the tumor distance using multiple lines that reflect the anorectal curvature [2,6,[18][19][20][21][22][23][24]29]. However, in our study, the direct methods using a straight line demonstrated the best results; this corroborates the findings by Meylemans et al, who compared measurement methods using a straight line or multiple straight lines [19].…”
Section: Discussionsupporting
confidence: 90%
“…In the recent study, different methods were used to measure the tumor distance from the anal verge on sagittal MRI. Although the majority of research groups have used multiple straight lines from the anal verge along [6,18,19] or not along [2,[20][21][22][23][24] the anorectal centerline, others have used a single straight line [19,25]. Thus, there is no clear consensus on the measurement of tumor distance, and no prospective study has compared these methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that these different origins of colon tissue could contribute to CRC disease pathology by independent processes. Indeed, there is already evidence to indicate that the clinical characteristics and molecular profiles of gene and protein expression for CRC differ across these different tissue sites[ 21 , 22 , 23 , 24 ]. One previous study has already shown that the primary tumor location could serve as prognostic factor in metastatic CRC[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Universal standardization of rectal cancer MRI protocols and MRI reporting would greatly benefit the surgical community by facilitating a more effective exchange of knowledge between specialties. 17,18 Another limitation of our study included difficulty defining the true anal verge on MRI. Even amongs radiologic societies, identification of the anal verge on MRI is a controversial topic.…”
Section: Study Limitationsmentioning
confidence: 99%